Transcriptional Control of Th9 Cells: Role of Foxo1 in Interleukin-9 Induction - Malik, Sakshi; Awasthi, Amit (Frontiers in Immunology, 2018)
Interleukin (IL) 9-producing helper T (Th) 9 cells play a major role in contributing immunity against extracellular pathogens. In addition, the role of Th9 cells was demonstrated in the pathogenesis of allergic, skin, and intestinal inflammation. The functions of Th9 cells were further extended in antitumor immune response, as Th9 cells were suggested to be potent antitumor Th cells. Given the pleotropic functions of IL-9 in various pathophysiological conditions, it is essential to understand the differentiation and stability of Th9 cells and other IL-9-producing T cells. In addition to Th9 cells, Th2 and Th17 cells as well as induced Foxp3+ regulatory T cells (iTregs) cells also produce IL-9, but how IL-9 production is regulated in these cell types is not yet clearly defined. Although Th2, Th9 and Th17 cells as well as iTregs develop in the presence of distinct differentiating factors, yet they all express IL-9 together with their own lineage specific cytokines. Here, in this review, we summarize the current understanding of signaling pathways that lead to the promotion of differentiation of Th9 cells and IL-9 induction in Th2 and Th17 cells, as well as in iTregs. We further discuss the transcriptional regulation of Th9 cells in context of Foxo1, as an essential transcription factor required for the development and functions of Th9 and other IL-9-producing T cells.